2020
DOI: 10.7759/cureus.8028
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Hip Spica Casting to Short Leg Casts and Bar after Hip Reconstruction in Cerebral Palsy

Abstract: Truong et al. This is an open access article distributed under the terms of the Creative Commons Attribution License CC-BY 4.0., which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Recently, Truong et al compared spica casting to short-leg Petrie casting in patients with CP following hip reconstruction [ 16 ]. They found no difference in hip stability, narcotic pain medication usage, or complication profile.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, Truong et al compared spica casting to short-leg Petrie casting in patients with CP following hip reconstruction [ 16 ]. They found no difference in hip stability, narcotic pain medication usage, or complication profile.…”
Section: Discussionmentioning
confidence: 99%
“…They noted that it may be more important to use a spica cast for children with osteopenic bone at risk for implant failure, which is more common in non-ambulatory children. Truong et al suggested that there was no significant advantage in hip stabilization when comparing use of spica versus Petrie immobilization, but that more children who received spica casting experienced femoral fragility fractures [ 16 , 19 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Albrektson et al compared the two methods in a retrospective review of 21 patients with CP or other genetic syndromes undergoing hip surgery and concluded that spica casts should be used in patients with osteopenia or instability in the early post-operative period ( 21 ). Truong et al demonstrated similar pain and complication profiles in children treated in spica casts versus short leg casts linked with a bar ( 27 ). Modern internal fixation has proven reliable in maintaining the alignment and compression of osteotomies during healing.…”
Section: Discussionmentioning
confidence: 98%
“…While hip spica casts were classically considered the standard for immobilization following hip reconstructive surgery in children with CP, there is evidence that satisfactory outcomes can be obtained with alternative methods of postoperative immobilization (19,24,25) (27). Modern internal fixation has proven reliable in maintaining the alignment and compression of osteotomies during healing.…”
Section: Discussionmentioning
confidence: 99%